Groupe Zaragoza. - Cassou, Jean (Paris : Galerie Raymond Creuze, 1967)
Asensio, Teo ; Sahun, Daniel ; Chueca, Otelo ; Santamaria, Ricardo ; Vera, Juan José
Groupe Zaragoza, Galerie Raymond Creuze, Paris, du 6 au 27 octobre 1967
boek
Keywords: Groupe Zaragoza